Physicochemical characterization of a lycopene-loaded mesoporous silica nanoparticle formulation - Carvalho, Gabriela Correa [UNESP]; Marena, Gabriel Davi [UNESP]; Carneiro Soares do Nascimento, Andre Luiz [UNESP]; Furquim de Camargo, Bruna Almeida [UNESP]; Sabio, Rafael Miguel [UNESP]; Lourenco, Felipe Rebello; Santos, Helder A.; Chorilli, Marlus [UNESP] (Wiley-Blackwell, 2024)
Lycopene (LYC), a carotenoid extracted mainly from tomatoes, has several biological properties, making its use desirable as a nutraceutical and pharmaceutical active ingredient. Among its various applications vulvovaginal candidiasis stands out. However, the use of LYC in therapy has limitations related to its solubility and stability. In this study, mesoporous silica nanoparticles (MSNs) are used to load and protect LYC from degradation. The exact amount of drug incorporated was determined by analytical techniques, such as high-performance liquid chromatography (HPLC) and thermal analysis. For this, we developed and validated an HPLC method for LYC quantification and evaluated LYC impregnation in MSNs, followed by thermogravimetry analysis (TGA). Differential scanning calorimetry (DSC) was also used in order to confirm drug incorporation. Additionally, an in vitro release study in simulated vaginal fluid was also carried out. The HPLC method was duly validated for the range of 26-125 mu g mL-1 and proved to be suitable for LYC quantification. DSC measurements suggest an improvement in the stability of the impregnated drug, which was reinforced by the release assay. Overall, the developed method is suitable to quantify LYC-loaded porous materials enabling its use in vaginal applications. This study showed that the analytical and pharmacotechnological development process of a nanoformulation composed of lycopene loaded in mesoporous silica nanoparticles for vulvovaginal candidiasis treatment was carried out satisfactorily. Furthermore, it is noteworthy that the loading process proved to be efficient in increasing both the aqueous solubility and stability of this drug, limiting factors for its application in therapy. image
Keywords: high-performance liquid chromatography; lycopene; mesoporous silica nanoparticles; thermogravimetry; validation